MECHANICAL REGENERATION OF SAND WASTE - D. I. Gnir; E. V. Govinchik (Литьë и металлургия)
The experimental activation of the sand regenerator of the firm SINTO is carried out at ОАО “MZOO". It is shown that sand grains are cleared from films of binding agents, that allows to use the treated sand for preparation of agglutinant and core sands.